Electrical property of macroscopic graphene composite fibers prepared by chemical vapor deposition. (21st May 2018) - Sun, Haibin; Fu, Can; Gao, Yanli; Guo, Pengfei; Wang, Chunlei; Yang, Wenchao; Wang, Qishang; Zhang, Chongwu; Wang, Junya; Xu, Junqi
Abstract: Graphene fibers are promising candidates in portable and wearable electronics due to their tiny volume, flexibility and wearability. Here, we successfully synthesized macroscopic graphene composite fibers via a two-step process, i.e. first electrospinning and then chemical vapor deposition (CVD). Briefly, the well-dispersed PAN nanofibers were sprayed onto the copper surface in an electrified thin liquid jet by electrospinning. Subsequently, CVD growth process induced the formation of graphene films using a PAN-solid source of carbon and a copper catalyst. Finally, crumpled and macroscopic graphene composite fibers were obtained from carbon nanofiber/graphene composite webs by self-assembly process in the deionized water. Temperature-dependent conduct behavior reveals that electron transport of the graphene composite fibers belongs to hopping mechanism and the typical electrical conductivity reaches 4.59 × 10 3 S m −1 . These results demonstrated that the graphene composite fibers are promising for the next-generation flexible and wearable electronics.